Orta bilim beriw mekteplerinde qaraqalpaqstan tariyxi páninde oqiwshilarġa tariyxiy bilimlerdi qáliplestiriw usillari hám áhmiyeti (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the process of formation of schoolchildren’s knowledge in history on the example of the subject "History of Karakalpakstan " and performing these tasks by teachers.